Analysis of licensing law on business services based on the Online Single Submission (OSS) system - Willi Otra Bismar; Soerya Respationo; Erniyanti Erniyanti; Fadlan Fadlan; Ramlan Ramlan; Parameshwara Parameshwara (Annals of Justice and Humanity, 2022)
Purpose: The purpose of this research is to examine the analysis of business licensing through OSS after the issuance of Government Regulation Number 24 Year 2018 and to analyze the perspective of OSS licensing implementation in the licensing system at PTSP Batam City. Research Methodology: The research method used in this research is normative research method by involving analysis of legal regulations, policies, and legal instruments related to applicable laws and regulations. Results: The result of the research shows that licensing before PP No. 24 Year 2018 was manual and took too long to process, licensing after PP No. 24 Year 2018 is effective can be online and can take place at any time of registration. For legal protection for business actors by adjusting the license to OSS so as not to lose money in order to establish relationships with third parties. Because there are no strict sanctions for business actors who do not make adjustments to OSS. Implementation: The existence of overlapping regulations and the non-realization of certainty of authority governing licensing between the regulations of the Regional Government Law, the Investment Law and PP Number 24 of 2018.